Evaluación de factores de riesgo laboral en el proceso de fabricación de bloques en el barrio San Felipe, cantón Latacunga, provincia de Cotopaxi, periodo 2014 – 2015 - Ibarra Salazar, Karina Fernanda (2015)
This research was developed in the San Felipe neighborhood of Latacunga Canton, seeing the need to identify and assess occupational risk factors to which workers are exposed in the manufacturing process of blocks. This researching was performed at the San Felipe neighborhood of Latacunga Canton, looking for the necessity to identify and assess the occupational risk factors which workers are exposed in the manufacturing process of grit bricks. Through a Check- List and Matrix NTP: 330 the risks were identified which exposed people that work at slab place; Which are: physical, chemical, ergonomic, electrical, mechanical and psychosocial, to its further evaluation in order to develop a safety manual….